AN INTERFERENCE-IMMUNE COMMUNICATION SYSTEM FOR DIGITAL DATA TRANSMISSION BASED ON A MULTI-CHANNEL CORRELATOR Part 1. DEVELOPMENT OF A SIGNAL FORMATION AND DECODING ALGORITHM FOR THE SUB-NOISE COMMUNICATION SYSTEM - Varavin, A. V.; Yermak, H. P.; Kudryavtsev, D. P.; Vasiliev, O. S.; Balaban, M. V.; Melnyk, S. S.; Zheltov, V. M.; Fateev, O. V. (Видавничий дім «Академперіодика», 2025)
Subject and Purpose. The work aims to develop and study an interference-immune radio communication system for transmitting and receiving digital information and video images using a Software-Defined Radio (SDR).Methods and Methodology. The processes of generation, reception, and decoding of broadband pseudorandom signals formed by the Direct Sequence Spread Spectrum (DSSS) technology are mathematically modeled. Basic software solutions are experimentally developed for data receiving, transforming, processing, and displaying. The functional capabilities of the hardware and software tools are evaluated and analyzed for their subsequent integration into the system. Results. An algorithm has been developed for generating and decoding from a sub-noise spread spectrum correlation communication system using DSSS technology. The processes of data formation and transmission by noise-like signals based on the Gold codes have been modeled. An algorithm for noise-like signal identification has been developed, based on the mathematical determination of the autocorrelation function which evaluates the relationship (degree of similarity) between the signal and its time-shifted copy. To maintain the phase coherence between the expected (received from air) and reference (key) signals at any time, a cyclically operating multi-channel correlator was developed. We estimated the maximum radio data rates over the radio channels when transmitting low-frequency telemetry signals, control signals, and video signals.Conclusions. The research and development of digital communication channels using signal coding through the Direct Sequence Spread Spectrum (DSSS) method along with Gold codes have demonstrated the potential to create compact devices for establishing interference-immune and low-noise multi-channel communication which is particularly suitable for data transmission in modern environments.Keywords: communication system, interference-immune communication, DSSS technology, Gold codes, multi-channel correlator, SDR receiver, digital streamManuscript submitted  25.07.2024Radio phys. radio astron. 2025, 30(1): 011-022REFERENCES1. Kamilo, F., 1995. Wireless Digital Communications: Modulation and Spread Spectrum Applications. India, Prentice-Hall of India Pvt. Limited.2. Gold, R., 1967. Optimal binary sequences for spread spectrum multiplexing. IEEE Trans. Inf. Theory, 13(4), pp. 619—621. DOI: https://doi.org/10.1109/TIT.1967.10540483. Ipatov, V.P., 2004. Spread Spectrum and CDMA. Principles and Applications. Wiley. DOI: https://doi.org/10.1002/04700918004. Simon, M., Omura, J.K., Scholtz, R.A., Levitt, B.K., 1994. Spread Spectrum Communications Handbook. NY McGraw-Hill.5. Proakis, J.G., Salehi, M., 2008. Digital Communications. 5th ed. McGraw-Hill, New York.6. Dillinger, M., Madani, K., Alonistioti, N., 2003. Software Defined Radio: Architectures, Systems and Functions. Wiley & Sons.7. Rami, A., Dezfouli, B., 2018. Software-defined Radios: Architecture, State-of-the-art, and Challenges. Comput. Commun., 128, Sept., pp. 106—125. DOI: https://doi.org/10.1016/j.comcom.2018.07.0128. Perepelitsyn, A., Shulga, D., 2012. FPGA Technologies in Medical Equipment: Electrical Impedance Tomography. In: Proc. of IEEE EastWest Design & Test Symposium (EWDTS). Kharkov, Ukraine, 14—17 Sept. 2012, pp. 43—440.9. Kulanov, V., Kharchenko, V., Perepelitsyn, A., 2009. Parameterized IP Infrastructures for Fault-Tolerant FPGA-Based Systems: Development, Assessment, Case-Study. In: Proc. of IEEE East-West Design & Test Symposium (EWDTS). 2009, pp. 322—325.10. Mazurkov, M., Sokolov, A., 2015. Recurrent synthesis methods of the sequences with optimal peak-to-average power ratio value of walsh-hadamard spectrum. Informatics and Mathematical Methods in Simulation, 5(3), pp. 203—209.11. Avdeyenko, G., 2020. Generating DVB-S2 Signals by Application of Nuand BladeRF x40 SDR Transceiver. In: 2020 IEEE Int. Conf. on Problems of Infocommunications. Science and Technology (PIC S&T). Kharkiv, Ukraine, 6—9 Oct. 2020, pp. 177—181. DOI: https://doi.org/10.1109/PICST51311.2020.9467904